2014
DOI: 10.1186/s13058-014-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital mammographic density and breast cancer risk: a case–control study of six alternative density assessment methods

Abstract: IntroductionMammographic density is a strong breast cancer risk factor and a major determinant of screening sensitivity. However, there is currently no validated estimation method for full-field digital mammography (FFDM).MethodsThe performance of three area-based approaches (BI-RADS, the semi-automated Cumulus, and the fully-automated ImageJ-based approach) and three fully-automated volumetric methods (Volpara, Quantra and single energy x-ray absorptiometry (SXA)) were assessed in 3168 FFDM images from 414 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
163
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 31 publications
8
163
2
2
Order By: Relevance
“…15 All approaches have shown that breast density is a significant risk factor for breast cancer. 16,17 However, for breast density information to be used consistently for assessing risk and tailoring screening pathways, it is essential that methods of assessment are reliable and reproducible, as inaccurate calculation could adversely affect the patient outcome and clinical management. The BI-RADS approach commonly used in the clinical practice is subjective and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…15 All approaches have shown that breast density is a significant risk factor for breast cancer. 16,17 However, for breast density information to be used consistently for assessing risk and tailoring screening pathways, it is essential that methods of assessment are reliable and reproducible, as inaccurate calculation could adversely affect the patient outcome and clinical management. The BI-RADS approach commonly used in the clinical practice is subjective and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Quantra has been shown to be an reliable 117,118 and reproducible 119,120 for mammographic breast density assessment, and a strong predictor of breast cancer risk from breast density. 28 Quantra has also been shown to accurately reproduce radiologists' BIRADS assessment on a two-category scale. 121,122 Volpara TM (Matakina Technology Limited) is also based on relative physics principles, and measures mammographic breast density by finding a reference point of entirely fat (P FAT ) in each image and then estimating X-ray attenuation relative to that point for all other points in the image.…”
Section: Categorisation Of Breast Composition Using "Quantitative Arementioning
confidence: 93%
“…87 For example, it encourages users to inform patients that small lesions may be missed in BIRADS C and that mammography sensitivity is lower in category D. 89 Previous editions of BIRADS have demonstrated consistent association between breast density and cancer risk particularly in postmenopausal women. 28,82 However, BIRADS suffers from reduced reproducibility and has shown wide inter-reader agreement (κ) ranging from 0.37 -0.91. [90][91][92] Therefore, an assessment of the extent of inter-reader agreement with the 5 th edition is increasingly relevant.…”
Section: The History Of Qualitative Breast Density Classificationmentioning
confidence: 99%
See 2 more Smart Citations